An unusual cause of knee pain in a young patient; hydatid disease of femur - Kuyucu, Ersin; Erdil, Mehmet; Dulgeroglu, Ali; Kocyigit, Figen; Bora, Arslan (My University, 2012)
INTRODUCTION: Osseous hydatid disease is a rare pathology and its differential diagnosis can be difficult.